Desain Sistem Pembangkit Listrik Hybrid Off-Grid Menggunakan Software HOMER Untuk Elektrifikasi Di Desa Suryawangi Kecamatan Labuhan Haji Kabupaten Lombok Timur - Hidayatullah, Harsandi; Adhevina, Ihda; Muljono, Agung Budi (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2024)
Energy and environmental problems are major challenge in the world. These problems related to the need to replace conventional fuels with new renewable energy sources. New renewable energy is scattered throughout Indonesia, including geothermal, wind, solar, hydro, and biomass. However, the utilization in the national energy is still low. This study offers a solution to this problem by planning a hybrid powerplant in Suryawangi Village, East Lombok, to serve the electrical energy needs of the village. In this study, solar and microhydro powerplant will be simulated to provide electrical energy using HOMER software. The data needed in this study was taken from BPS data and the global solar atlas. Suryawangi village has hydro energy potential with a 477,97 liters per seconds of Kokok Tebaban water flow and also 4,725 kWh/m2/day solar radiation at coordinates -8Â°39'49" S, 116Â°34'43" E which has potential to be source for solar powerplant. Simulation results shows the hybrid powerplant system with 20,7 kW capacity of microhydro powerplant and 229 kW capacity of solar plant cost a total of Rp. 689.721.500,- with cost of energy Rp. 377,52 and operating cost Rp. 9.197.444,-. The hybrid powerplant system generates total energy of 434.259 kWh/year, where the solar powerplant generates 321.295 kWh/year and the microhydro powerplant generates 112,964 kWh/year of energy.